Evaluasi Resistensi Gulma Berdaun Lebar terhadap Herbisida di Perkebunan Sawit dan Pengembangan Strategi Pengendalian yang Efektif - Pratama, Alfindo; Djaingsastro, Aulia Juanda (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
Weeds in oil palm plantations negatively affect the quantity and quality of fresh fruit bunches, inhibit plant growth, increase susceptibility to pests and diseases, interfere with water use, and raise production costs. This study aimed to identify dominant broadleaf weed species, evaluate herbicide resistance, determine weed regrowth time, and develop effective control strategies. A factorial randomized block design with 6 treatments and 2 controls was applied, with observations conducted every 7 days for 6 weeks. Results showed that the most dominant broadleaf weed was Synedrella nodiflora with a dominance level of 27.64%, while the lowest population was Asystasia intrusa at 12.36%. Herbicide application significantly increased weed mortality compared to the control, with paraquat treatment (P3) producing the fastest response, reaching early visible damage within hours and higher mortality rates (>50% by day 5). Resistance analysis indicated that weeds were still susceptible, with Resistance Index (RI) values of 1.53 (glyphosate) and 0.80 (paraquat). Weed regrowth began at 16 days after application (H+16), dominated by Ageratum conyzoides, Physalis minima, and Synedrella nodiflora. An effective weed control strategy involves maintaining proper application intervals and using low herbicide doses to delay resistance development.